THE ROLE OF ALIMENTARY HYPERSENSITIVITY IN EARLY FORMATION OF ATOPIC STATUS IN INFANTS - T.V. Turti; L.S. Namazova-Baranova; G.V. Yatsyk; E.P. Zimina ("Paediatrician" Publishers LLC, 2011)
High incidence of different types of allergy in children forces us to study the atopy formation peculiarities and methods of its effective prophylaxis. The objective: to study the peculiarities of formation of alimentary allergy in infants. Methods: the study included newborns. Authors studied the family history of allergic diseases. The process of allergy development in system «mother-fetus-child» and influence of several risk factors were detected. Results: authors showed the role of hereditary factor, excessive use of food with high sensitizing potential, artificial feeding with mixtures containing cow milk proteins, and deviations in formation of normal intestinal micro biocenosis in atopy formation in children. Conclusion: authors proposed the method of revelation children with high risk of alimentary allergy. Obtained data proves the necessity of stage-by-stage combined measures for the prophylaxis of allergic pathology in ontogenesis. Key words: newborns, atopy, alimentary allergy, IgE. (Voprosy sovremennoi pediatrii - Current Pediatrics. 2011; 10 (4): 10-15)